Mastering bioactive coatings of metal oxide nanoparticles and surfaces through phosphonate dendrons. (5th February 2020) - Nguyen, Dinh-Vu; Hugoni, Ludivine; Filippi, Miriam; Perton, Francis; Shi, Da; Voirin, Emilie; Power, Laura; Cotin, Geoffrey; Krafft, Marie-Pierre; Scherberich, Arnaud; Lavalle, Philippe; Begin-Colin, Sylvie; et al.
Abstract : Dendritic phosphonates are versatile coatings of several nanomaterials for health applications ranging from implants to nanoparticles and microbubbles. Abstract : We reported herein an efficient method for constructing dendritic bisphosphonic acid tweezers of generation 1 and 2, which have been proven as versatile surface coatings for metal oxides implants or nanoparticles. These dendritic structures were successfully utilized for different purposes: (i) biocompatible coverings for iron oxide nanoparticles through in vitro assays, (ii) antifouling surface coatings for silica through quartz crystal microbalance studies, and (iii) stabilizing ligands for magnetic nanoparticle–microbubble conjugates via preliminary Langmuir monolayer studies.